Effect of Tributyltin on the Sex Ratio in Guppy (Poecilia reticulata) - Seval Dernekbaşı; İsmihan Karayücel; Olcay Kırıkoğlu (Aquatic Sciences and Engineering)
In this study, the effect of tributyltin (TBT) on the sex ratio in guppy (Poecilia reticulata) during the labile period covering both embryonic and post hatching periods was investigated. The gravid females was fed an artificial diet containing TBT chloride at an environmental levels of 25, 50 and 150ng/g feed from 16th day after the first parturition until next parturition. The newly hatched larvae from untreated females were also fed by the same diet for 11 days. TBT caused various abnormalities like body shape and fin deformations in gravid females and no parturition was seen. The male ratio significantly increased to 70.74, 87.50 and 87.18 % in the experimental groups of guppy larvae fed by 25, 50 and 150ng TBT/g diet, respectively. Survival and growth of the larvae were negatively affected by TBT treatment. These results clearly showed the masculanization of guppy exposed to TBT for the first time.